Phase transitions and upconversion luminescence in oxyfluoride glass ceramics containing Ba4Gd3F17 nanocrystals. Issue 4 (April 2017) - Krieke, Guna; Sarakovskis, Anatolijs; Ignatans, Reinis; Gabrusenoks, Jevgenijs
Abstract: Novel transparent Er 3+ doped oxyfluoride glass-ceramics containing Ba4 Gd3 F17 nanocrystals were prepared by melt quenching followed by heat treatment of as-prepared glasses. The phase composition and microstructure were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Intense upconversion luminescence (UCL) was detected. Longer characteristic decay times and splitting of the luminescence bands compared to the precursor glass indicated the incorporation of erbium ions in the crystalline phase. The spectroscopic properties of glass ceramics were compared with single phase cubic and rhombohedral Ba4 Gd3 F17 ceramics. The unit cell parameters and atomic positions in the rhombohedral phase were calculated using Rietveld refinement. The local environment of Er 3+ and the phonon energy of both polymorphs were analyzed using luminescence and Raman spectroscopy. In the glass ceramics, a phase transition from distorted metastable fluorite to ordered rhombohedral Ba4 Gd3 F17 was observed and resulted in the enhancement of the efficiency of UCL.